3D manufacturing of intracranial aneurysm biomodels for flow visualizations: Low cost fabrication processes. (July 2020) - Souza, A.; Souza, M.S.; Pinho, D.; Agujetas, R.; Ferrera, C.; Lima, R.; Puga, H.; Ribeiro, J.
Abstract: There is a continuous search for better and more complete in vitro models with mechanical properties closer to in vivo conditions. In this work a manufacturing process, based on a lost core casting technique, is herein reported to produce aneurysm biomodels to perform experimental hemodynamic studies. By using real artery images combined with a lost core casting technique, three materials were tested: paraffin, beeswax and glycerin-based soap. All in vitro biomodels were compared according to their transparency and final structure. Additionally, comparisons between experimental and numerical flow studies were also performed. The results have shown that the biomodels produced with beeswax and glycerine-based soap were the most suitable in vitro models to perform direct flow visualizations of particulate blood analogue fluids. The biomodels proposed in this works, have the potential to provide further insights into the complex blood flow phenomena happening at different kinds of pathologies and answer to important hemodynamics questions that otherwise cannot be tackled with the existing in vitro models. Highlights: Manufacture PDMS biomodels with low-cost lost core casting materials. These materials allow to manufacture channels with diameters less than 2 mm. Lost core casting materials can be removed from PDMS biomodels using water. PDMS biomodels with high level of transparency to be used experimentally. The PDMS biomodels are used to validate numerical simulations. Graphical abstract: Image, graphical abstract